2010
DOI: 10.1177/0040517510391698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different extraction methods on fiber quality of nettle (Urtica dioica L.)

Abstract: Chemical extraction, water retting, microbiological and enzymatic methods were applied on entire nettle stalks and/or unretted decorticated fiber of a selected fiber nettle clone. Morphological and mechanical properties and chemical composition were then determined on fiber samples. The first interesting result concerned the good degree of separation between fibers and shives obtained by mechanical scutching applied on stalks stored for 1 year, probably resulting from natural retting processes occurring during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…After 40 years, the plants (30 clones) Bredemann bred during that period were started to be cultivated again at the Institute of Applied Botany, Hamburg, Germany between 1992 and 1995 (Dreyer et al, 1996). planting density and crop age Recently stinging nettle has become the subject of scientific interest in many countries throughout Europe: Austria, Germany, Finland, United Kingdom, the Netherlands, Italy, Latvia and Lithuania (Bacci et al, 2010;Bisht et al, 2012). The first investigations of stinging nettle in Lithuania gave promising results (Jankauskienė, Gruzdevienė, 2008;2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 40 years, the plants (30 clones) Bredemann bred during that period were started to be cultivated again at the Institute of Applied Botany, Hamburg, Germany between 1992 and 1995 (Dreyer et al, 1996). planting density and crop age Recently stinging nettle has become the subject of scientific interest in many countries throughout Europe: Austria, Germany, Finland, United Kingdom, the Netherlands, Italy, Latvia and Lithuania (Bacci et al, 2010;Bisht et al, 2012). The first investigations of stinging nettle in Lithuania gave promising results (Jankauskienė, Gruzdevienė, 2008;2013).…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibres have gained renewed interest over the last decade due to their varied uses in textiles, composites, handicrafts, packaging, etc., and consumer demand for environmentally sustainable and traceable processing chains (Bacci et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic development of the nettle processing community of Nepal has been through proper marketing strategy and exporting the fashion textile and handicraft products to Europe and America. Bacci et al [10] also supported that for sustainable handicraft products from nettle it is very essential to go for enzymatic retting to obtain best quality fibre. Deokota and Chhetri [34], reported in their research the handloom and handicrafts are moved side-by-side to promote nettle-based products in Nepal.…”
Section: Nettle For Sustainable Traditional Handicraftsmentioning
confidence: 94%
“…They concluded that considering the environmental impact and other related aspects, the enzymatic process is the best among these three methods of fibre separation of nettle fibres whereas the chemical treatment leads to environmental pollution and steam explosion required huge amount of heat energy. Considering the above aspects, Bacci et al [10] have experimented different methods of retting and fibre extraction. From their studies it can be confirmed that both controlled microbiological retting with the combined use of anaerobic and aerobic bacteria and vat enzymatic retting, especially when a solution of Pectinex Ultra SP-L with EDTA (ethylene di-amine tetraacetic acid) was used, led to improvement in fibre quality.…”
Section: Extraction Methods Of Nettle Fibrementioning
confidence: 99%